Correction criteria for the qualitative analysis of the prison population: drugs possession/consumption and gender violence - Muñoz-López, Lucas; Fernández García-Valdecasas, Borja; López-Rodríguez, Slava; Aguilar-Yamuza, Beatriz (Frontiers in Psychiatry, 2024)
People with language difficulties cannot face challenges related to social skills. Those language disorders affect academic, work environments, and social interaction, leading to maladaptive and aggressive behaviors. Young inmates are at high risk of experiencing unrecognized language deficiencies. It is, therefore, necessary to analyze linguistic pathologies that can influence criminal behavior (drugs possession/consumption and gender violence crimes). There are many standardized tests to evaluate and detect language difficulties in adults in English. However, there are relatively few options in Spanish; there are no tests that evaluate language qualitatively and in depth. Most of the research is conducted with children and adolescents. Objetives: to propose a reliable coding system for the correction and interpretation of narratives (essays and narratives) from the Battery for the Evaluation of Writing Processes (PROESC) in the prisoners charged of drugs possession or consumption and gender violence crimes. Design: The sample was composed of 287 men. Main Outcome Measures: They completed the Demographic, Offense, and Behavioral Interview in Institutions, the International Personality Disorders Examination (IPDE), and PROESC. Results: We found that the proposed coding system presented high concordance, that is, high inter-rater reliability. Conclusion: The classification system for the correction and interpretation of narratives was shown to be reliable.